Relationship between nonalcoholic fatty liver disease and liver fibrosis risk scales with overweight and obesity scales in 219,477 spanish workers - Martínez-Almoyna Rifá, Emilio; Tomás Gil, Pilar; Coll Villalonga, Josep Lluis; Ramírez Manent, José Ignacio; López-González, Ángel Arturo (My University, 2023)
Introducción: La Enfermage del hígado graso no alcohólico (EHGNA) es una patología altamente prevalente y de etiología multifactorial que puede terminar en fibrosis hepática. El objetivo de este estudio es valorar la asociación entre escalas de riesgo de EHGNA y fibrosis hepática y escalas de sobrepeso-obesidad. Material y métodos: Estudio descriptivo y transversal en 219477 trabajadores españoles en los que se determina la relación entre los valores de diferentes escalas de riesgo de EHGNA como Fatty liver index (FLI), Hepatic steatosis index (HSI), Zhejian University index (ZJU), Fatty liver disease index (FLD), Framingham steatosis index (FSI), Lipid accumulation Product (LAP) y fibrosis hepática (BARD score) con valores de escalas de sobrepeso-obesidad (índice cintura/altura, índice de masa corporal, Clínica Universitaria de Navarra Estimador de grasa corporal (CUN BAE) y Metabolic Score for Visceral Fat (METS-VF). Resultados: Tanto los valores medios como la prevalencia de valores de alto riesgo de presentar EHGNA y fibrosis hepática son más elevados en las personas con obesidad determinados con todas las escalas. Las prevalencias más elevadas se obtienen al aplicar las escalas de BMI y CUN BAE. Conclusión: Se confirma la estrecha relación entre los valores de diferentes escalas de riesgo de EHGNA y fibrosis hepática con los valores de escalas de sobrepeso-obesidad.

Introduction: Non-alcoholic fatty liver disease (NAFLD) is a highly prevalent pathology of multifactorial etiology that can lead to liver fibrosis. The aim of this study is to assess the association between NASFLD and liver fibrosis risk scales and overweight-obesity scales. Material and methods: Descriptive and cross-sectional study in 219477 Spanish workers in which the relationship between the values of different NASH risk scales such as Fatty liver index (FLI), Hepatic steatosis index (HSI), Zhejiang University index (ZJU), Fatty liver disease index (FLD), Framingham steatosis index (Framingham steatosis index), Zhejiang University index (ZJU) and Fatty liver disease index (FLD) was determined, Framingham steatosis index (FSI), Lipid accumulation Product (LAP) and liver fibrosis (BARD score) with values of overweight-obesity scales (waist/height index, body mass index, Clínica Universitaria de Navarra Body Fat Estimator (CUN BAE) and Metabolic Score for Visceral Fat (METS-VF). Results: Both the mean values and the prevalence of high-risk values for NASH and liver fibrosis are higher in people with obesity determined with all the scales. The highest prevalences are obtained when applying the BMI and CUN BAE scales. Conclusion: The close relationship between the values of different NASH and liver fibrosis risk scales and the values of overweightobesity scales is confirmed.
Artículos en revistas